High‐Performance Next‐Generation Perovskite Nanocrystal Scintillator for Nondestructive X‐Ray Imaging. Issue 40 (23rd August 2018) - Heo, Jin Hyuck; Shin, Dong Hee; Park, Jin Kyoung; Kim, Do Hun; Lee, Sang Jin; Im, Sang Hyuk
Abstract: Readily commercializable and cost‐effective next‐generation CsPbBr3 perovskite nanocrystals (PNCs) based X‐ray detectors are demonstrated. The PNCs‐based X‐ray detector exhibits higher spatial resolution (9.8 lp mm −1 at modulation transfer function (MTF) = 0.2 and 12.5–8.9 lp mm −1 for a linear line chart), faster response time (≈200 ns), and comparable stability (>40 Gyair s −1 of X‐ray exposure) compared with the commercialized terbium‐doped gadolinium oxysulfide (GOS)‐based detectors (spatial resolution = 6.2 lp mm −1 at MTF = 0.2 and 6.3 lp mm −1 for a linear line chart, response time = ≈1200 ns) because the PNCs‐based scintillator has ≈5.6‐fold faster average photoluminescence lifetime and stronger emission than the GOS‐based one. Abstract : A high‐performance next‐generation perovskite nanocrystal (PNC) scintillator is used for nondestructive X‐ray imaging. The high‐performance cheap CsPbBr3 PNCs scintillators are based on indirect X‐ray detectors with high‐resolution, sensitivity, and stability.